UJI SENSITIVITAS BAKTERI Escherichia coli TERHADAP ANTIBIOTIK PADA URIN PASIEN INFEKSI SALURAN KEMIH DI LABORATORIUM KLINIK BUNDA THAMRIN MEDAN - Rajagukguk, Tiara; Siahaan, Maniur Arianto; Aritonang, Erlan (UNIVERSITAS SARI MUTIARA INDONESIA, 2024)
Urinary tract infection disease is one of the most common health problems in the community, and the most common pathogenic cause is Escherichia coli bacteria. The purpose of this study was to determine the sensitivity of Escherichia coli bacteria to antibiotics in the urine of patients with urinary tract infections (UTI) at the Bunda Thamrin Clinical Laboratory. This research was conducted from March to May 2024 starting from literature search to writing research reports. The population in this study were all patients with UTI in March to May 2024 and the samples used were 10 samples. This study used two types of antibiotics, namely ciprofloxacin and gentamicin antibiotics. The method used in this study is the Escherichia coli examination method by culturing on Mac Concey Agar media and sensitivity testing using the Vitek 2 Compact tool. The results of the bacterial identification test showed that there was growth of Escherichia coli bacteria and Klebsiella sp. The results of the sensitivity test of Escherichia coli bacteria to antibiotics showed that Escherichia coli bacteria were still sensitive to gentamicin antibiotics by 75% and resistant by 25%. Antibiotic ciprofloxacin was resistant by 87.5% and intermediate by 12.5%.